Construindo as bases para a biofabricação de implantes regenerativos paciente-específico para reparação de lesões parciais dos meniscos do joelho: uma abordagem baseada em bioimpressão 3D. - (:unkn) unknown (Universidade Brasil, 2024)
The knee meniscus is a fibrocartilaginous structure essential to joint biomechanics, playing critical roles, fundamental to maintaining knee health and preventing cartilage degeneration. Meniscal injuries are common, and due to limited vascularization, have a low healing capacity, often requiring surgical intervention, such as partial meniscectomy. However, the lack of effective therapeutic options for partial lesions, which represent the majority of the cases, underscores the need for innovative alternatives, as these lesions are associated with early osteoarthritis development. This study aimed to develop a personalized regenerative implant for partial knee meniscus lesions, using 3D bioprinting guided by magnetic resonance imaging (MRI) and computer-aided design (CAD) software to replicate each patient’s specific meniscal lesion morphology. The methodology involved generating 3D digital models of the menisci based on MRI images, followed by lesion modeling performed in Fusion 360 software, where the intact contralateral meniscus was mirrored to guide the lesion 3D model construction in the injured meniscus. After the modeling phase, implant fabrication was carried out using GelMA-based hydrogel with 3D extrusion bioprinting. The printed implant was then subjected to quantitative morphological analysis using structured light 3D scanning and GOM Inspect metrology software to evaluate its accuracy against the digital model, ensuring the morphological fidelity necessary for replicating meniscal tissue. Next, an ex vivo proof of concept was conducted, in which implants obtained by the same technique were implanted in porcine menisci with controlled lesions, allowing for visual and quantitative evaluation of implant structural adaptation in various lesions geometries, encompassing different sizes and locations in the meniscus. The results showed high fidelity between the implant and the digital model, with an average deviation of less than ±1.5 mm in deviation analysis and precise adaptation in ex vivo tests, suggesting that our approach has clinical potential for the fabrication of patient-specific meniscal implants. These findings underscore the feasibility of 3D bioprinting as a promising alternative in knee regenerative medicine.
Keywords: Menisco; Engenharia tecidual; Impressão tridimensional; Modelagem paciente-específica.; Bioengenharia